PENDAMPINGAN STANDARISASI GURU TAMAN PENDIDIKAN AL-QUR’AN MELALUI PELATIHAN METODE TILAWATI BERBASIS ASET - Rusdiana (Kalam Nusantara Institute, 2023)
A teacher of the Qur’an Education is required to determine the rigt method of learning the Qur’an. In addition, it takes skill and skill that is standart in implementing Qur’anic learning. Therefore, it is necessary to mentoring the standardization of Qur’anic learning throught training, among other trainings in Tilawati method. This mentoring is done by the asset approach in the framework of asset-bassed-Community Development ( ABCD). Performance Achievment in this mentoring is the empowerment of religious leaders and society in providing accomodation and consumption. Community assets were successfully empowerment to support the program’s success.